Analysis of Independent Curriculum Management Methods (Merdeka) for Children with Special Needs - Rasyad, Muhammad Ghaffar; Suklani, Suklani; Kambali, Kambali (CV. Strata Persada Academia, 2025)
This study explores the management methods of the Independent Curriculum (Merdeka Curriculum) for children with special needs (CSN) in Indonesia, emphasizing its flexibility and individualized learning approach. The research aims to evaluate the curriculum's effectiveness in supporting CSN's holistic development while addressing key challenges such as limited resources, teacher training, and the need for adaptive instructional strategies. Using a qualitative, descriptive-exploratory design, data were collected from special schools and inclusive schools through in-depth interviews, participatory observations, and document analysis. Participants included teachers, school principals, parents, and supporting professionals. The findings reveal that implementing the Merdeka Curriculum enhances inclusivity and individual potential by providing tailored educational strategies, particularly through the development of Individualized Education Programs (IEPs). However, challenges such as resource constraints, insufficient training, and limited collaboration with stakeholders were identified as barriers to optimal implementation. The study highlights the importance of adaptive teaching methods, flexible assessment systems, and enhanced coordination among educators, caregivers, and professionals to maximize CSN’s development. This research contributes both theoretically and practically by offering insights into inclusive curriculum management and providing actionable recommendations for educators, policymakers, and stakeholders.